2010
DOI: 10.1038/nature09349
|View full text |Cite
|
Sign up to set email alerts
|

2010 Maule earthquake slip correlates with pre-seismic locking of Andean subduction zone

Abstract: The magnitude-8.8 Maule (Chile) earthquake of 27 February 2010 ruptured a segment of the Andean subduction zone megathrust that has been suspected to be of high seismic potential. It is the largest earthquake to rupture a mature seismic gap in a subduction zone that has been monitored with a dense space-geodetic network before the event. This provides an image of the pre-seismically locked state of the plate interface of unprecedentedly high resolution, allowing for an assessment of the spatial correlation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
351
1
8

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(380 citation statements)
references
References 44 publications
20
351
1
8
Order By: Relevance
“…Some studies of the 2010 Maule earthquake support this hypothesis (Moreno et al, 2010;Pulido et al, 2011), even though the debate is still active as other studies indicate a limited overlap between seismic gap and coseismic slip (Lorito et al, 2011). A comparison of several source models for the Maule earthquake show, however, that there is a large uncertainty on the location of regions of large slip (i.e., Delouis et al, Figure 10.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some studies of the 2010 Maule earthquake support this hypothesis (Moreno et al, 2010;Pulido et al, 2011), even though the debate is still active as other studies indicate a limited overlap between seismic gap and coseismic slip (Lorito et al, 2011). A comparison of several source models for the Maule earthquake show, however, that there is a large uncertainty on the location of regions of large slip (i.e., Delouis et al, Figure 10.…”
Section: Discussionmentioning
confidence: 94%
“…In recent years, the development of Global Positioning System (GPS) and satellite radar interferometry make it possible to measure the strain buildup associated with plate coupling in many earthquakeprone regions around the world (Chlieh et al, 2004(Chlieh et al, , 2011Béjar-Pizarro et al, 2013). Recent studies have suggested that subducting plates are either locked or creeping aseismically, and that a patchwork of locked or coupled regions during the interseismic period may be related with asperities of earthquakes (Konca et al, 2008;Moreno et al, 2010;Perfettini et al, 2010;Loveless and Meade, 2011). In this study, we propose a methodology to characterize source models of future megathrust earthquakes based on the spatial distribution of interseismic coupling (ISC) of subduction zones as well as information of historical earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers are resistant to failure and do not show microseismicity during the inter-seismic period. When a barrier finally ruptures, surrounding areas can catch up with plate motions, leading to activation of sub-faults and segments 27 region of high locking gradient and ended up releasing most of the stress accumulated along its fault plane since the last major event 28 . We suggest that such a scenario may apply to the Princes Island and Marmara segments of the NAFZ.…”
Section: Discussionmentioning
confidence: 99%
“…C: Vertical displacements. ), green: Moreno et al (2012), orange: Delouis et al (2010, Bouguer anomaly and interseismic coupling distribution from Moreno et al (2010). Location of the profile is shown in Fig.…”
Section: S U P P O Rt I N G I N F O R M At I O Nmentioning
confidence: 99%